2009
DOI: 10.1590/s1677-55382009000600008
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of the acute scrotum: is there a place for contrast-enhanced ultrasonography?

Abstract: Purpose: To present and evaluate the findings of contrast-enhanced ultrasonography (CEUS) in typical cases of acute painful scrotum. Materials and Methods: Nineteen patients aged from 19 to 61 years old were included in the study. All patients underwent grey-scale and color Doppler ultrasonography (US) of the scrotum, followed by imaging after i.v. administration of 2.4 mL of a second generation ultrasound contrast agent (microbubbles of sulphur hexafluoride). Α dedicated, contrast-sensitive technique was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 21 publications
1
44
0
3
Order By: Relevance
“…Moschouris et al [13] examined a series of 19 patients with a painful scrotum, 6 of whom had a history of trauma, concluding that there was not a significant advantage over conventional colour Doppler ultrasound. However the assessment of perfusion and tissue viability was not an important goal of the study.…”
Section: Hedayati M E Sellars D M Sharma and P S Sidhumentioning
confidence: 99%
“…Moschouris et al [13] examined a series of 19 patients with a painful scrotum, 6 of whom had a history of trauma, concluding that there was not a significant advantage over conventional colour Doppler ultrasound. However the assessment of perfusion and tissue viability was not an important goal of the study.…”
Section: Hedayati M E Sellars D M Sharma and P S Sidhumentioning
confidence: 99%
“…The contrast media is administered intravenous (2.4-4.8 ml), followed by a 10 ml saline solution bolus. After approximately 20 seconds, the microbubbles reach the intravascular space of the testis and may be visualized in the testicle up to 2-3 minutes after administration, then the intensity progressively decreases (wash-out phenomenon) [2][3][4][5]. CEUS presents an added diagnosis value in the acute pathology of the scrotum, being superior to non-contrast US, with a sensitivity (Se) and a specificity (Sp) up to 95% and 100, respectively (ultrasound has an 76% Se and a 45 Sp) [2].…”
Section: Introductionmentioning
confidence: 99%
“…[32]. To our knowledge, there are no reports in the literature on the use of CEUS to evaluate blunt scrotal trauma (with the exception of a few anecdotal reports, including some by our group [14,18,20]. Valentino et al [20] reported on the use of CEUS for emergency work-up of scrotal pathology.…”
Section: Discussionmentioning
confidence: 89%
“…Early reports on the use of CEUS in the work-up of scrotal pathology indicated that it could be used to identify abscesses and areas of necrosis, which appear as nonenhanced areas [13,14]; to document increases in the mean contrast-medium transit time in the presence of a varicocele [15]; to evaluate tumor vascularization [16]; to facilitate extraction of sperm from infertile patients (by pinpointing better perfused areas of the gonad) [17]; and to characterize and follow-up ambiguous cases of segmental ischemia [18]. Testicular trauma could thus represent a new field of application for CEUS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation